ABC analysis a current management state of the hotel enterprises in the Republic of Kazakhstan - Suraganova, S.K.; Bissekov, A.; Bekbulatova, A. (KSU Publ., 2013)
The modern hospitality industry represents global on the scales the complete, integrated and dynamic branch of the services sector which is entirely based on the principles of market economy, objective regularities of the international division of labor and production internationalization. Growth of the hotel economy was outlined in the Republic of Kazakhstan only with town planning development after its joining to Russia. After October revolution by development of production and non-productive spheres construction of hotels approached to their modern shape in Karaganda and Almaty the majority from which functioned in the conditions of planned managing began. In this article is used the method of the ABC analysis for more exact consideration of a condition of the hotels services market in present conditions of economic development of the Republic of Kazakhstan.
Қазақстан Республикасында мейманханалық кəсiпорындардың қазiргi күйiн басқарудың ABC-талдауы
ABC-анализ современного состояния управления гостиничными предприятиями в Республике Казахстан
Keywords: Republic of Kazakhstan; ABC analysis; tourism; hospitality; hotel business; management; hotel enterprises